Prosedur Pemeriksaan Lopografi Proksimal Dan Distal Pra Operasi Duhamel Pull Through Di Instalasi Radiologi RSUD Banyumas - Elza Afrita Sari; Arnefia Mei Yusnida; Ayu Mahanani (Journal of Innovation Research and Knowledge, 2026)
Background: Loopography is typically performed using AP plain, AP post-contrast, lateral post-contrast, RPO, LPO, and AP post-evacuation projections. The primary contrast medium is barium sulfate. However, if perforation or obstruction is suspected, a water-soluble contrast medium is considered safer. At the Radiology Department of RSUD (Regional General Hospital) Banyumas, proximal and distal loopography is performed using AP plain, AP post-contrast, and lateral post-contrast projections with barium sulfate as the contrast medium. This study aimed to describe the examination procedure, the rationale for using a limited number of projections, and the rationale for selecting barium sulfate as the contrast medium for preoperative proximal and distal loopography before Duhamel pull-through surgery at RSUD Banyumas. Methods: This study employed a qualitative method with a case study approach conducted from September 2025 to April 2026 at the Radiology Department of RSUD Banyumas. Data were collected through observation, interviews, and documentation involving one radiologist and three radiographers. Results: The examination procedure began with patient preparation, followed by an AP plain abdominal radiograph, administration of the contrast medium through the distal and proximal stomas, and evaluation of the post-contrast radiographs using AP and lateral projections. Barium sulfate, diluted at a ratio of 1:4, was used because it provided clearer visualization of the colonic lumen and anatomy than water-soluble iodinated contrast media. The AP and lateral projections were considered sufficient for evaluating the colonic lumen and distal colonic anatomy before surgery. The ALARA principle was implemented through the use of high-kV techniques, appropriate collimation, and proper patient positioning to minimize radiation exposure. Conclusion: Preoperative proximal and distal loopography before Duhamel pull-through surgery at RSUD Banyumas is performed using AP and lateral projections with barium sulfate as the contrast medium because it provides clear visualization of the colon, is more cost-effective, and supports the implementation of the ALARA principle to minimize radiation exposure.